2009
DOI: 10.1007/s00436-009-1506-x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Coccidiosis – Investigations on the Cellular Immune Response against Isospora suis

Abstract: Porcine neonatal coccidiosis is caused by the protozoan Isospora suis and affects mainly piglets in the first three weeks of life. High morbidity with diarrhoea and reduced weight gain lead to economic losses, affecting pig-breeding worldwide. Infection causes damage of the mucosal surface in the jejunum and ileum and transient non-haemorrhagic diarrhoea. Secondary infections with other enteric pathogens may lead to increased mortality. Despite its economic and veterinary importance, the immunology of porcine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…While mean fecal consistencies remained below 1.2 in group Wien-20, all other groups developed increased mean fecal scores after infection, indicating enteritis as a consequence of parasite replication [50]. Diarrhea was observed in all groups except group Wien-20, but prevalences and numbers of diarrhea days were generally low.…”
Section: Discussionmentioning
confidence: 90%
“…While mean fecal consistencies remained below 1.2 in group Wien-20, all other groups developed increased mean fecal scores after infection, indicating enteritis as a consequence of parasite replication [50]. Diarrhea was observed in all groups except group Wien-20, but prevalences and numbers of diarrhea days were generally low.…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that PCMV infection might exacerbate porcine respiratory disease complex (PRDC) [27] and other diseases in growers due to its immunosuppressive effect [25,28,29]. PCMV mainly affects the immune function of T lymphocytes and macrophages [28,29] and it is assumed that resistance to C. suis and other coccidia is mainly based on cellmediated immunity [7,30]. Recent research has shown that PCMV induces changes in the transcriptome of the porcine thymus involving immune-related signalling pathways [29] and the micro-RNA expression of infected macrophages, mainly involved in immune and metabolic processes [28].…”
Section: Discussionmentioning
confidence: 99%
“…Isospora suis ) causes intestinal infections which may cause transient diarrhoea mostly in the second week of life. Due to the peculiarities of the porcine neonatal immune system (see below) and the strong age resistance to C. suis in piglets older than three weeks [46, 47], it is currently assumed that only pigs older than six weeks can mount an appropriate immune response. For this and other reasons vaccination of piglets against C. suis is not considered feasible.…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%
“…At the time of birth the porcine immune system is poorly developed (for review see [47]); intestinal Peyer’s patches contain almost no immune cells and the gut epithelium and subepithelial tissues are only completely populated with T- and B-cells and antigen-presenting cells at about six weeks of age, leaving ample time for pathogens to establish and reproduce. At the same time, the gut microbiota are establishing and infections with pathogens at a very early age may have a number of consequences beyond transient parasite infection.…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%
See 1 more Smart Citation